2010
DOI: 10.1002/pi.2931
|View full text |Cite
|
Sign up to set email alerts
|

Production, cellular structure and thermal conductivity of microcellular (methyl methacrylate)–(butyl acrylate)–(methyl methacrylate) triblock copolymers

Abstract: Microcellular foaming of a (methyl methacrylate)-(butyl acrylate)-(methyl methacrylate) triblock copolymer was carried out by means of supercritical C0 2 in a single-step process. The experiments were performed at 40 C using a pressure of 300 bar (30 MPa) during 24 h. The depressurization times were modified from 2 to 30 min, leading to cell sizes from 10 to 100 \im, and relative densities from 0.11 to 0.17. It was found that the key parameter to control cell size and density was depressurization time: longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Nanometric cell sizes wer not obtained, but the cell size decreased by more than one decade compared with the iso-density MAM foams in Reglero-Ruiz and colleagues' study [16]. This foaming batch process was carried out in another study by Murray and colleagues [128], for 1.5mm thick plaques of ABS.…”
Section: Figure 20 -[53]mentioning
confidence: 88%
See 3 more Smart Citations
“…Nanometric cell sizes wer not obtained, but the cell size decreased by more than one decade compared with the iso-density MAM foams in Reglero-Ruiz and colleagues' study [16]. This foaming batch process was carried out in another study by Murray and colleagues [128], for 1.5mm thick plaques of ABS.…”
Section: Figure 20 -[53]mentioning
confidence: 88%
“…The authors [16] had already shown that the foaming of MAM copolymers led to low-density foams with micro-cells, whose growth was not restrained. However, MAM copolymers can also act as nucleating agents in a polymer/copolymer blend.…”
Section: Figure 20 -[53]mentioning
confidence: 98%
See 2 more Smart Citations
“…Both models considered conduction through the gas and solid phases in the foam. Bauer proposed a more comprehensive model by including convective heat transfer [5], which was later shown only significant when the pore size was greater than 3 mm [14]. The radiation effect was included in a few models, as discussed in [6, 7].…”
Section: Introductionmentioning
confidence: 99%